1993
DOI: 10.1038/363361a0
|View full text |Cite
|
Sign up to set email alerts
|

Leukaemia inhibitory factor is necessary for maintenance of haematopoietic stem cells and thymocyte stimulation

Abstract: Leukaemia inhibitory factor (LIF) has a variety of effects on different cell types in vitro, inhibiting the differentiation of embryonic stem cells and promoting the survival and/or proliferation of primitive haematopoietic precursors and primordial germ cells. Here we show that LIF-deficient mice derived by gene targeting techniques have dramatically decreased numbers of stem cells in spleen and bone marrow. Injection of spleen and marrow cells from these mice promotes long-term survival of lethally irradiate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
188
0
1

Year Published

1996
1996
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 356 publications
(197 citation statements)
references
References 24 publications
8
188
0
1
Order By: Relevance
“…47,48 Using LIF-deficient mice, Escary et al 49 demonstrated that LIF is required to maintain survival of hematopoietic stem cells (but not their terminal differ- entiation) and that thymic T cells require LIF to respond to concanavalin A, an observation possibly linked to the finding that LIF is required to maintain a functional thymic epithelium. 19 For human lymphocytes, release of LIF appears to be specific to T cells and to CD4 þ T cells in particular.…”
Section: Lif In T Cellsmentioning
confidence: 99%
“…47,48 Using LIF-deficient mice, Escary et al 49 demonstrated that LIF is required to maintain survival of hematopoietic stem cells (but not their terminal differ- entiation) and that thymic T cells require LIF to respond to concanavalin A, an observation possibly linked to the finding that LIF is required to maintain a functional thymic epithelium. 19 For human lymphocytes, release of LIF appears to be specific to T cells and to CD4 þ T cells in particular.…”
Section: Lif In T Cellsmentioning
confidence: 99%
“…57,58 Deficiencies in stem cells and committed progenitors resembling the WT1 defect have also been described for mice lacking the thrombopoietin (TPO) receptor c-mpl and for mice lacking the growth factors interleukin-6 (IL-6), kit ligand and Lif, and the HOX cofactor Pbx1. 57,[59][60][61][62] Hematopoietic defects of WT1-deficient mice could be the consequence of the failure of regulation by WT1 of one or more hematopoietic signaling pathways. If receptor expression levels are reduced by the absence of WT1, a hematopoietic phenotype resembling the WT1-negative hematopoietic cell would be expected.…”
Section: Discussionmentioning
confidence: 99%
“…Mice lacking LIF [28,29] or the LIF receptor (LIFR) do not have an obvious cardiac phenotype [30]. This suggests that LIFR-independent members of this cytokine family are sufficient to support normal cardiac development.…”
Section: Discussionmentioning
confidence: 99%
“…The gp130 cytokine family is characterized by functional redundancy, and the phenotypes of mice lacking individual cytokines [12,17,28,29,45] are much less severe than the phenotypes of mice lacking their shared receptors [10,30,46]. Nonetheless, the early and robust expression of CT-1 in the developing heart tube, and the sustained expression of CT-1 in the adult heart, suggested that CT-1 played a unique role in promoting cardiac myocyte survival and hypertrophy during development and after injury.…”
Section: Discussionmentioning
confidence: 99%